Childbirth-Associated Fistula and Perineal Tears Repaired on Outreach Campaigns in Remote Democratic Republic of Congo - Paluku J; Bruce P; Kamabu E; Kataliko B; Kasereka J; Dube A (International Journal of Women's Health, 2021)
Justin Paluku,1,2 Phoebe Bruce,3 Eugénie Kamabu,4 Benjamin Kataliko,1 Jonathan Kasereka,5 Annie Dube3 1Department of Obstetrics and Gynecology, HEAL Africa Tertiary Hospital, Goma, North Kivu, Democratic Republic of Congo; 2Department of Obstetrics and Gynecology, University of Goma (UNIGOM), Goma, North Kivu, Democratic Republic of Congo; 3Department of Undergraduate Medical Education, Northern Ontario School of Medicine, Sudbury, Ontario, Canada; 4Department of Internal Medicine, HEAL Africa Tertiary Hospital, Goma, North Kivu, Democratic Republic of Congo; 5Department of Surgery, HEAL Africa Tertiary Hospital, Goma, North Kivu, Democratic Republic of CongoCorrespondence: Justin PalukuDepartment of Obstetrics and Gynecology, HEAL Africa Tertiary Hospital, P.O. Box 319, Goma, Democratic Republic of CongoEmail justin.paluku@healafrica.orgPurpose: To describe the demographics and evaluate the repair of childbirth-associated injuries leading to incontinence in patients in remote Democratic Republic of Congo (DRC).Patients and Methods: Four surgical outreach campaigns were organised between March 2018 and October 2019. These campaigns specifically targeted women with incontinence secondary to childbirth-associated injuries. Patients were recruited on a voluntary basis, and locations included Katako-kombe (Sankuru province), Wamba (Haut Uelé province), Karawa (North Ubangi province) and Kipaka (Maniema province). Necessary care was provided along with informal teaching with local healthcare professionals.Results: A total of 481 patients,14– 71 years old with a mean of 32 years of age, were included in this study. The average duration of incontinence associated with a childbirth injury was 6.8 years. Vesicovaginal fistulas (277/481; 57.6%) and perineal tears (148/481; 30.8%) were predominant, while the combination of vesicovaginal and rectovaginal fistulas were seen in only 5 (1.0%) patients. Vaginal delivery (259/481; 53.9%), caesarean section (120/481; 25.0%) and laparotomy (hysterectomy) (102/481; 21.2%) were identified as the causes of the fistulas treated during the surgical campaign. Vesicovaginal fistulas were more likely to require complex repairs, as compared to rectovaginal fistulas and perineal tears (P-value < 0.0001). As well, vesicovaginal fistulas were less likely to result in successful resolution of the incontinence when compared to rectovaginal fistulas and perineal tears (P-value < 0.0001).Conclusion: Vesicovaginal fistulas are predominant among childbirth injuries encountered in remote DRC with poorly managed vaginal deliveries being the leading cause. Cure rate of fistulas and perineal tears is high during outreach campaigns; however, long-term follow-up is limited. There remains a need to train and mentor rural medical professionals in the DRC on adequate management of obstetric emergencies.Keywords: vesicovaginal fistula, rectovaginal fistula, perineal tears, childbirth injuries